Penerapan Model Pembelajaran Make A Match terhadap Hasil Belajar IPS Kelas IV Siswa - Susilowati, Yulia; Hamdan, Hamdan; Frima, Aren (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
This study aims to determine the completeness of learning outcomes of grade IV students of SD Negeri 2 Wonosari after using the Make A Match learning model. The method used is a quantitative method with a Pre-experimental Design research design in the one group pre-test-post-test category. The sampling technique used is saturated sampling. The data collection technique uses an multiple choice test. Data analysis techniques consist of prerequisite analysis techniques and hypothesis testing. The prerequisite analysis testing technique uses a normality test while the hypothesis used is the z-test. The results showed that the average pre-test was 62.012 with a percentage of completeness of 13.64% or 3 students who completed it while the average post-test was 73.701 with a percentage of 81.82% or 18 students who completed it. The results of the z-test analysis obtained a -value (2.36) > -table (0.4909). The conclusion is that the application of the Make A Match learning model on the social studies learning outcomes of grade IV students of SD Negeri 2 Wonosari is significantly complete. Keywords: Application, Make A Match, Social Studies Learning Outcomes